Comments on the priority of Fryxelliella paciﬁca over Fryxelliella sepulvedana (Eupodiscaceae, Bacillariophyta) - Hernández-Becerril, David U.; Barón-Campis, Sofía A. (Phytotaxa, 2014)
In 2008 two new species of the diatom genus Fryxelliella A.K.S. Prasad, Riddle et Livingston (1997: 306) were independently described from the tropical Mexican Pacific Ocean: Fryxelliella pacifica Hernández-Becerril et Barón-Campis (Hernández-Becerril & Barón-Campis 2008: 150) and F. sepulvedana Meave, Zamudio et Fernandes (Meave et al. 2008: 179). The types of both species were collected at Salina Cruz, Oaxaca, Mexico.